Comparison of Streptococcus pneumoniae isolates occurring in optochin-susceptible and optochin-resistant variants by analyzing whole-genome sequencing data - Vohrnová, Sandra; Kozáková, Jana; Honskus, Michal (Microbiology spectrum, 2025)
Globally, among the most fundamental tests used for the identification of Streptococcus pneumoniae isolates is determining susceptibility to optochin. In the last 2 decades, optochin-resistant strains have been frequently reported in the literature, which can lead to the misidentification of S. pneumoniae . This study compares whole-genome sequencing data of optochin-susceptible and optochin-resistant subpopulations of S. pneumoniae isolates and investigates the genetic probable causes of resistance in the genomes of optochin-resistant subpopulations.